1984
DOI: 10.1007/bf00008619
|View full text |Cite
|
Sign up to set email alerts
|

A stressed stream ecosystem: macroinvertebrate community integrity and microbial trophic response

Abstract: A year-long study of a second-order stream in Southwestern Virginia was carried out from 1979-80 . One of the objectives of the study was to evaluate the effects of sewage and electroplating plant effluent stress on the trophic response of aquatic invertebrate assemblages and microbial communities in the stream . Quantitative benthic samples were collected periodically at three reference stations and four stressed stations below the outfalls . Invertebrates were counted, identified taxonomically, and classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…According to Wallace and Merritt (1980) some species of benthos were found in high number when algal productivity was maximum. The present findings are in conformity with the studies of Olive andDambach (1973), Brightman andFox (1976) and Kondratieff et al (1984) that benthic invertebrates were concentrated in areas in the streams and wetlands receiving organic waste. Dehghani et al (2007) also observed that sewage maturation ponds are appropriate for the growth and development of aquatic insects especially species of Diptera and Hemiptera.…”
Section: Benthic Faunasupporting
confidence: 94%
“…According to Wallace and Merritt (1980) some species of benthos were found in high number when algal productivity was maximum. The present findings are in conformity with the studies of Olive andDambach (1973), Brightman andFox (1976) and Kondratieff et al (1984) that benthic invertebrates were concentrated in areas in the streams and wetlands receiving organic waste. Dehghani et al (2007) also observed that sewage maturation ponds are appropriate for the growth and development of aquatic insects especially species of Diptera and Hemiptera.…”
Section: Benthic Faunasupporting
confidence: 94%
“…These diverse demands on water resources, combined with forest management practices, place severe stresses on these streams. Major anthropogenic disturbances include: sewage and industrial effluents (e.g., Kondratieff et al 1984, Kondratieff and Simmons 1982, Tarter 1976; clearcut logging (Silsbee and Larson 1983, Tebo 1955, Webster et al 1983) and associated road-building (Lenat et al 1981); mining practices (Tarter 1976), which often result in acid drainage problems (Samuel et al 1978); dam construction; and potential susceptibility to acidic precipitation (Lynch and Dise 1985). In the southeastern Piedmont, major anthropogenic disturbances include: urbanization (Benke et al 1981); channelization; agriculture and grazing; logging, including associated road construction (Lenat et al 1975); and dam construction for hydroelectric generation, recreational use, and water storage.…”
Section: Geographical Patterns Of Disturbance: Anthropogenic Activitiesmentioning
confidence: 99%
“…The magnitude and nature of the impact are expected to vary with distance from the discharge (Hynes, 1960;Kondratieff et al, 1984). For example, DO depletion effects will be greatest some distance downstream, whereas ammonia toxicity and particulate matter smothering effects will be maximal near the discharge.…”
Section: Ss Increase (G M" A)mentioning
confidence: 99%